Brittle-to-ductile transition in high temperature pre-stretched polycarbonate - Wu, Xuelian (2023)
The brittle-to-ductile transition is investigated in polycarbonate (PC) after different types of thermomechanical treatment. In addition to the stress versus strain curves in uniaxial stretching to fracture of the original, preheated, shape recovered and high temperature pre-stretched samples, photoelasticity is applied to reveal the internal stress field in the fracture samples and high temperature pre-stretched samples. The change in microstructure after pre-deformation is concluded to be the reason behind the brittle-to-ductile transition. However, the type of subsequent loading to fracture is also important to determine if there is any transition. The magnitude of pre-deformation, the temperature of pre-deformation and the maximum deformation capability of the original material are three major parameters that affect the significance of brittle-to-ductile transition.